The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.ympev.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

False phylogenies on wood mice due to cryptic cytochrome-b pseudogene

Abstract: a b s t r a c tThe phylogeny and phylogeography of the Old World wood mice (subgenus Sylvaemus, genus Apodemus, Muridae) are well-documented. Nevertheless, the distributions of species, such as A. fulvipectus and A. ponticus remain dubious, as well as their phylogenetic relationships with A. sylvaticus. We analysed samples of Apodemus spp. across Europe using the mitochondrial cytochrome-b gene (cyt-b) and compared the DNA and amino-acid compositions of previously published sequences. The main result stemming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Morphological species determination was confirmed by PCR and sequencing of the partial mitochondrial cytochrome b (cyt b) gene (Fink et al 2010, Schlegel, et al 2012b. Rodent species and genetic affiliations within species were determined by sequence comparisons against GenBank entries using the BLAST algorithm (www.ncbi.nlm.nih.gov) and against species-specific cyt b datasets covering all genetic lineages within these rodents (Michaux et al 2003, Heckel et al 2005, Michaux et al 2005, Dubey et al 2009, Wójcik et al 2010, Sutter et al 2013). …”
Section: Rodent Trapping and Necropsymentioning
confidence: 99%
“…Morphological species determination was confirmed by PCR and sequencing of the partial mitochondrial cytochrome b (cyt b) gene (Fink et al 2010, Schlegel, et al 2012b. Rodent species and genetic affiliations within species were determined by sequence comparisons against GenBank entries using the BLAST algorithm (www.ncbi.nlm.nih.gov) and against species-specific cyt b datasets covering all genetic lineages within these rodents (Michaux et al 2003, Heckel et al 2005, Michaux et al 2005, Dubey et al 2009, Wójcik et al 2010, Sutter et al 2013). …”
Section: Rodent Trapping and Necropsymentioning
confidence: 99%
“…These 151 polymorphic sites included a total of 157 mutations, 134 of which were parsimonyinformative. Considering the recent data about presence of pseudogenes in phylogeographic assessments (Dubey et al 2009), the sequences were checked for the presence of stop codons and chimeric sequences. No stop-codon insertions or deletions were observed in the alignment.…”
Section: Sequence Datamentioning
confidence: 99%
“…Despite this advantage, incorrect assignments of nucleotide sequences in the GenBank were found to be disturbingly frequent (Reutter et al 2003). The problem stemmed from two sources: undetected cryptic pseudogenes in the alignment (Dubey et al 2009) and a long known morphological crypsis with subsequent misclassification of samples. As a consequence, a number of fundamental questions concerning species boundaries in Apodemus remain open, particularly so in the western Palaearctic (Hoofer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted with a DNeasy blood and tissue kit (Qiagen) following the manufacturer's protocol. A quick survey of available literature [6,7,[9][10][11][12][13] and data stored in GenBank, showed that barcoding marker Cytochrome B would allow discrimination between the four Apodemus candidates. For amplification of Cyt B, universal primers L14724 and H15915 [14] (Table 1) were ordered, but given the condition of the specimen, there was serious doubt that the DNA would not be too degraded to directly amplify a fragment of almost 1200 basepairs.…”
Section: Methodsmentioning
confidence: 99%
“…The branch support values were obtained by standard maximum likelihood (ML) bootstrapping (100 replicates, no model specified). GenBank accession-numbers of selected sequences as well as well as the provenance of the corresponding specimens and a reference to their original publication [6][7][8]10,13,[17][18][19][20] are shown next to the taxon-labels (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%